Incidencia de la contribución de los productores cacaoteros a la recaudación tributaria del cantón Caluma, provincia Bolívar año 2016 Darwin Alfredo Rivadeneira Echeverria - Aguilar Mestanza, Diana Maricela (2016)
This report of research work is in the problem of the system of trouble in the incidence of contribution of cocoa sector calumeño and surroundings belonging to the province Bolivar, in order to determine which are the causes of noncompliance with tax obligation to market the product by performance indicators. The present research word is the first study performed in cocoa sector on the incidence of contribution of cocoa to the canton Caluma tax revenue producers, the results will be advantageus to promote a tax culture in this sector. The research was conducted to producers of cocoa in the rural sector of the canton and marketers of cocoa located in the urban sector, for the development of this study we take as a basis the above by: Alejandro Najera Martinez on the subject of contribution, Gabriela Rios Granados referring to the topic tax collection and also to Alejandro Saldaña Magallanes with the issue of tax liability. The methodology used in the study allowed us to investigate the process of commercialization of cocoa to meet the current development when selling cocoa and determine the influence of these processes on tax contribution Caluma.